Effects of Colemanite and Fiber Types on Strength and Water Absorption of Mortar Mixtures Containing Air-Entraining Admixture - Ozansoy, Ayse Irem; Ozen, Suleyman (Mdpi, 2025)
The global construction industry heavily relies on cementitious systems, which are a major contributor to carbon dioxide emissions due to the energy-intensive nature of cement production. These emissions account for approximately 8% of global CO2 output, exacerbating climate change and environmental degradation. The global reliance on cementitious systems has led to substantial carbon dioxide emissions during cement production, intensifying the need for environmentally sustainable alternatives. Turkey, which holds 73% of the world's boron reserves, offers a unique opportunity to explore boron-based minerals like colemanite as potential replacements for cement. In this study, the effects of colemanite (a boron mineral) and four fiber types-steel, basalt, carbon, and polypropylene-on the compressive strength, flexural strength, and water absorption of mortar mixtures incorporating air-entraining admixtures were investigated. All mixtures contained 0.1% air-entraining admixture (by cement weight), with fixed parameters: a water/binder ratio of 0.485, a sand/binder ratio of 2.75, and slump-flow values of 190 +/- 20 mm. Cement was partially replaced with colemanite at 3% and 5%, while fibers were added at 0.5% by volume. Fresh-state properties (slump-flow and admixture requirements) and hardened-state properties (28-day compressive/flexural strength and water absorption) were evaluated. Selected samples underwent SEM analysis for microstructural assessment. Key findings revealed that both colemanite and fibers increased admixture demand to achieve target slump flow. While colemanite and fibers collectively enhanced compressive strength, their interactions varied: basalt and carbon fibers exhibited superior performance in mixtures without colemanite, whereas steel fibers showed greater efficacy in colemanite-containing mixtures. The strength increase was less pronounced when colemanite was introduced to mixtures containing carbon, polypropylene fibers, and basalt. The trend of flexural strengths was comparable to that of compressive strengths. SEM images revealed that the void distribution in the samples, influenced by the effects of colemanite and fibers, had a more dominant effect on compressive and flexural strengths. Water absorption inversely correlated with mechanical performance. This study not only contributes to reducing the carbon footprint of cementitious systems by partially replacing cement with colemanite but also provides practical insights to optimize the use of fibers to increase strength performance and reduce water absorption properties from durability parameters. These findings support the development of more sustainable and durable materials.
Keywords: colemanite; steel fiber; carbon fiber; basalt fiber; polypropylene fiber; compressive and flexural strengths; water absorption